PROFIL OSMOTIK GELONDONGAN IKAN BANDENG (Chanos chanos Forsskal) SELAMA PROSES KULTIVASI DI TAMBAK BANDENG DESA WONOREJO KABUPATEN KENDAL - Anita Karolina; Sutrisno Anggoro; Supriharyono Supriharyono (JURNAL PERIKANAN TROPIS, 2020)
Milkfish is  euryhaline fish that can live in wide range salinity, so it will affect with osmoregulation processes. This research aimed to examine the osmotic response of milkfish fingerling during cultivation processes in brackishwater ponds at Wonorejo Village district of Kendal. The  research was conducted on July-October  2016. The cultivation process of milkfish fingerling has been cultured for 60 days in 2000 m2 brackishwater pond. The initial density of milkfish larvae was 100 individuals /m2 with a lenght size of 10 mm on average and 15 days old. Samples of milkfish fingerling were taken on the 20th, 40th and 60th days, the number of samples was 3 individuals every size. The measurement result of blood osmolarity was 460, 05 to 490.10 mOsm / l H2O higher than media osmolarity 38,98 – 194,5 mOsm/l H2O. The osmotic response of  milkfish fingerling were hyperosmotic to the hypotonic environment and osmoregulator fish.